Free electron lasers based on LINAC-800 - Alexandrov, V.S.; Balalykin, N.I.; Kobets, V.V.; Meshkov, I.N.; Minashkin, V.F.; Seleznev, I.A.; Sergeev, A.P.; Shirkov, G.D.; Sidorov, G.I.; Syresin, E.M.; Tokareva, N.A.; Tiutiunnikov, S.I. (Вопросы атомной науки и техники, 2006)
The project “FELs and LINAC-800” is being under development at JINR. It is based on an accelerator facility
presented to JINR by NIKHEF, Amsterdam. Analysis has shown that it is possible to build in Dubna a universal
light source with unique characteristics consisting of a complex of Free Electron Lasers (FEL) covering continuously
the wavelength range from far-infrared (150 µm) down to ultraviolet (150 nm). Besides, LINAC-800 could be
used for different applications and as an injector for the next generation synchrotron radiation source. Проект ЛСЭ и ЛИНАК-800 реализуется в ОИЯИ. Он основан на ускорительном оборудовании, предоставленном ОИЯИ NIKHEF (Амстердам). Анализ показывает, что в Дубне станет возможным сооружение универсального источника с уникальными характеристиками, состоящего из комплекса лазеров на свободных электронах (ЛСЭ), покрывающих непрерывно длины волн от дальнего инфракрасного излучения (150 мкм) до ультрафиолета (150 нм). Проект ЛСЕ і ЛІНАК-800 реалізується в ОІЯД. Він заснований на прискорювальному устаткуванні, що було дано ОІЯД NІKHEF (Амстердам). Аналіз показує, що в Дубні стане можливим спорудження універсального джерела з унікальними характеристиками, що складається з комплексу лазерів на вільних електронах (ЛВЕ), що перекривають безперервно довжини хвиль від далекого інфрачервоного випромінювання (150 мкм) до ультрафіолету (150 нм).